Eccrine Porocarcinoma: Clinical and Histopathological Study of 14 Patients with Special Emphasis on Sentinel Lymph Node Biopsy - Anna-Stiina Meriläinen; Maria von Willenbrand-Bäckmann; Harri Sihto; Virve Koljonen (Medical Journals Sweden, 2023)
Eccrine porocarcinoma is a rare skin adnexal tumour that affects elderly people. Most eccrine porocarcinomas are stage I or II according to the American Joint Committee on Cancer. The prognosis is good in early stages, but worsens when advanced. Since information on the use of sentinel lymph node biopsy in these patients is scarce, this study examined the records of all patients with eccrine porocarcinoma treated at Helsinki University Hospital during a 17-year period and focused on sentinel lymph node biopsy patients. The study identified 14 patients (9 male, 5 female). There were 2 metastases to the lymph nodes and 2 recurrences at initial referral to our institution. All primary tumours had wide local excision and 6 patients also had sentinel lymph node biopsy, of whom none had positive lymph nodes. There were no new metastases or recurrences during follow-up. Three patients died of causes other than eccrine porocarcinoma. When comparing the wide local excision only and wide local excision with sentinel lymph node biopsy groups, no parameters reached statistical significance. The decision process of the multidisciplinary tumour board meeting on whether to perform sentinel lymph node biopsy was not clear, perhaps due to the limited knowledge of eccrine porocarcinoma. Further studies and international collaboration are warranted.